Evolution from the Network-Centric Warfare Сoncept to the Data-Centric Operation Theory (Advances in Military Technology, 2021)
The article analyzes the impact of disruptive technologies on the evolutionary development of military architectural frameworks and concepts of warfare. It argues the need for a transition from the Network-Centric Warfare concept to the Data-Centric Operation theory and proposes a 4D-extensional representation of the combat space of weapon systems integrated into a single network. It is concluded that there is hardware redundancy in modern weapon systems and it is possible to use it as a network resource, the management of which provides additional opportunities for improving operational capabilities.
Keywords: data-centric operation; network-centric warfare; 4D architecture; system of systems